Teoria obiektów abstrakcyjnych Edwarda N. Zalty. Analiza i krytyka - Grygianiec, Mariusz (Filozofia Nauki, 2005)
The paper offers a sketchy reconstruction of axiomatic foundations of Zalta's theory of abstract objects. The theory is based on Ernst Mally's distinction between two types of predication: an exemplification of properties and an encoding of properties. The author shows how the theory in question could be used to reconstruct in a satisfying way many other metaphysical theories e.g. the theory of Platonic Forms, the theory of situations, the theory of possible worlds. The paper also provides several critical comments to some presumptions and consequences of the analyzed metaphysical doctrine.